Minimizing sediment deposition in urban drainage channels in Ghana: Channel section design approach (Journal of Science and Technology, 2016)
The phenomenon of sediment deposition leading to the silting-up of drainage channels has been a majorproblem in the performance of urban drainage systems. Preventive and costly maintenance measures areoften employed to mitigate the problem. In the area of design, critical or self-cleansing velocity methodshave been used to achieve certain levels of flushing-out of sediment load in the channels. As analternative to the current design practices in Ghana, this study presents the channel section approach.Deposition of suspended sediment in channels takes place mainly because of velocity fluctuations in thechannel. In this study, therefore, a channel section capable of maintaining a constant vertical velocitydistribution is presented. The advantage of the constant velocity channel section is that it minimizes thevelocity fluctuations in the channel and subsequently reduces the deposition of sediment in the channel.